The moderating role of COMT gene rs4680 polymorphism between maladaptive metacognitive beliefs and negative symptoms in patients with schizophrenia - Feten Fekih-Romdhane; Georges Kerbage; Nagham Hachem; Michelle El Murr; Georges Haddad; Alexandre Andrade Loch; Rony Abou Khalil; Elissar El Hayek; Souheil Hallit (BMC Psychiatry)
Abstract Background Although the positive association between impairments in metacognitive capacity and negative symptoms in people with schizophrenia spectrum disorders is widely evidenced in the literature, the explaining mechanisms of this association are still less known and poorly understood. This study aims to bridge this knowledge gap by testing the hypothesis that COMT rs4680 variants will act as moderators in the relationship between certain metacognitive domains and negative symptoms’ severity. Method A cross-sectional study was carried-out during the period between February and March 2024. A total of 115 biologically unrelated Arab (Lebanese) patients with schizophrenia were included. Results After controlling for sex and duration of illness as a potential confounder, moderation analyses showed that the AG genotype of the COMT rs4680 served as a significant moderator between maladaptive metacognitive beliefs about cognitive confidence (i.e. lack of confidence in memory) and negative symptoms. In non-carriers of the COMT rs4680 AG genotype, lower cognitive confidence (i.e., more “lack of cognitive confidence”) is significantly associated with greater negative symptoms. Conclusion Findings suggest that metacognition may be a relevant treatment target in the management of negative symptoms particularly in non-carriers of the COMT rs4680 AG genotype. Therefore, genetic testing could potentially be used to match patients with metacognitive interventions that are more likely to be effective in supporting recovery from negative symptoms.